Gross negligence in the reckless driving of motor vehicles - Gaibor-Yánez, ítalo (2020)
The intent constitutes a hard to determine figure within criminal law, especially if it is intended to assess the intention of an individual at the time of committing a crime. Within this context, the objective of this paper is centered around gathering information about gross negligence, reckless driving, and if this is contemplated in Ecuadorian Legislation. To this end, it was necessary to resort to secondary information sources such as books, codes, laws, and articles, among others, to determine or not their application within the national context. Considering this background, it is possible to conclude that the study highlights the shortcomings of the country’s legal framework, both with the Ley Orgánica de Transporte Terrestre y Seguridad Vial whose last amendment corresponds to 2014 and the Código Orgánico Integral Penal (2014). In none of these regulations is there an article that punishes reckless driving based on gross negligence.